2016
DOI: 10.1186/s13012-016-0530-3
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of evidence summaries on health policymakers and health system managers use of evidence from systematic reviews: a systematic review

Abstract: BackgroundSystematic reviews are important for decision makers. They offer many potential benefits but are often written in technical language, are too long, and do not contain contextual details which make them hard to use for decision-making. There are many organizations that develop and disseminate derivative products, such as evidence summaries, from systematic reviews for different populations or subsets of decision makers. This systematic review aimed to (1) assess the effectiveness of evidence summaries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 31 publications
2
52
0
2
Order By: Relevance
“…One found that decisionmakers described summary of findings tables with event rates and absolute differences as preferable. 49 The other found that mailed bulletins with synopses of systematic reviews that were distributed to clinicians were associated with some practice improvement. 50 Wye 2015 studied the use of evidence by local policymaking bodies in the U.K. and noted that policymakers preferred verbal over written presentation.…”
Section: Tools For Promoting Use Of Evidence In Health System Decisionsmentioning
confidence: 99%
See 1 more Smart Citation
“…One found that decisionmakers described summary of findings tables with event rates and absolute differences as preferable. 49 The other found that mailed bulletins with synopses of systematic reviews that were distributed to clinicians were associated with some practice improvement. 50 Wye 2015 studied the use of evidence by local policymaking bodies in the U.K. and noted that policymakers preferred verbal over written presentation.…”
Section: Tools For Promoting Use Of Evidence In Health System Decisionsmentioning
confidence: 99%
“…In general, they preferred summaries that were brief, presented in a "graded" format (key messages, executive summary) or presented verbally. 11,18,22,35 Two systematic reviews 49,50 addressed decisionmakers preferences for various derivative products based on systematic reviews. One found that decisionmakers described summary of findings tables with event rates and absolute differences as preferable.…”
Section: Tools For Promoting Use Of Evidence In Health System Decisionsmentioning
confidence: 99%
“…The growing popularity of “decision supports,” such as checklists, protocols, and assessment routines, used as “boundary objects” aiming to overcome these knowledge boundaries (Allen ) has contributed to the greater standardization of decisions and practices at the organizational level (Rousseau and Gunia ). Other approaches synthesize bodies of evidence to provide actionable advice for decision makers, often in the form of structured summaries of research (Crowley and Scott ; Newman, Cherney, and Head ; Petkovic et al ). At the same time, excessive standardization has the potential to generate professional resistance (Martin et al ) and limit responsiveness to the ever‐changing context if it is used without reflection (Kislov et al ).…”
Section: Evolution Of the Evidence‐based Policy And Practice Movementmentioning
confidence: 99%
“…Por outro lado, os pesquisadores poderiam disseminar resultados de pesquisas empregando meios adequados ao público de interesse 8 . Portanto, além dos artigos científicos, os pesquisadores poderiam empregar outras formas e meios de disseminação do conhecimento, como infográficos, reuniões com a comunidade, vídeos e seminários de treinamentos 9 .…”
Section: Figuraunclassified